Intermedia phases in synthesis of AlPO4-5 molecular sieve: A study of XRD, raman scattering and TGA - Vien et al, Vo (Vietnam Journal of Chemistry, 2014)
In the world, aluminophosphate molecular sieves have been synthesized successfully; however, the intermediate phases and their evolution during crystallization process have not been studied systematically yet. In this work, the behaviors of the initial gel and the evolution of the intermediate phases during crystallization process of AlPO4-5 molecular sieve using triethylamine as a template have been investigated. It has been shown that in the amorphous aluminophosphate gel phases, template triethylamine does exist in protonated form; and there appear a significant change, formation of 12-member rings of AlPO4-5 structure, during the early stage of crystallization of AlPO4-5. In addition, a proposition to explain the crystallization of AlPO4-5 is also suggested.